Resolusi Konflik Masyarakat Melalui Pendidikan Sosial Perspektif Al-Quran - Nur Arfiyah Febriani; Nafisah Nafisah; Siti Mukjizatin (Kopertais Wilayah I DKI Jakarta dan Banten, 2022)
Conflicts that occur in the community, among others, are caused by intolerance towards differences in beliefs, this is what makes religion said to be a trigger for social tension. For this reason, the community needs to be educated to appreciate various differences, respect each other and support the progress of every member of the community. This research offers about social education from the perspective of the Koran which can be used as a reference to accommodate all kinds of differences and interests. Using the maudu'i interpretation method, this study reveals about social education for the community in the perspective of the Koran carrying the paradigm of integrated theocentric society. This is based on the description of the Qur'an that social education for the community emphasizes the dimension of unity even though there are many differences. This informal social education model is relevant to the concept of global citizenship education (GCE) or global community education which is applied in formal education. GCE is a UNESCO program aimed at students of all ages children, youth and adults.